2005
DOI: 10.1096/fj.05-4652fje
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline inhibits W7FW14F apomyoglobin fibril extension and keeps the amyloid protein in a prefibrillar, highly cytotoxic state

Abstract: A significant number of fatal diseases are classified as protein deposition disorders, in which a normally soluble protein is deposited in an insoluble amyloid form. It has been reported that tetracycline exhibits anti-amyloidogenic activity by inhibiting aggregate formation and disaggregating preformed fibrils. In this work, we examined the effect induced by the presence of tetracycline on the fibrillogenesis and cytotoxicity of the amyloid-forming apomyoglobin mutant W7FW14F. Like other amyloid-forming prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 62 publications
5
35
0
Order By: Relevance
“…The estimated percentages of secondary structure were: a 10%, b 37%, turn 22%, and unordered 31%. Similarly to what was observed with amyloidogenic proteins, mature fibrils formed by W7FW14F are not cytotoxic, whereas granular aggregates are (Sirangelo et al 2004;Malmo et al 2006). Two factors appear crucial for fibril formation in the case of W7FW14F apomyoglobin: noncovalent interactions and charge effects.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…The estimated percentages of secondary structure were: a 10%, b 37%, turn 22%, and unordered 31%. Similarly to what was observed with amyloidogenic proteins, mature fibrils formed by W7FW14F are not cytotoxic, whereas granular aggregates are (Sirangelo et al 2004;Malmo et al 2006). Two factors appear crucial for fibril formation in the case of W7FW14F apomyoglobin: noncovalent interactions and charge effects.…”
supporting
confidence: 51%
“…The cytoxicity of W7FW14F apomyoglobin aggregates was evaluated by the MTT assay. Soluble prefibrillar oligomers have been implicated as the primary toxic species of amyloids; a decrease in reduced MTT levels is generally observed in the presence of these species, whereas fibrils have little or no effect (Booth et al 1997;Kayed et al 2003;Stefani and Dobson 2003;Sirangelo et al 2004;Malmo et al 2006). In particular, we tested the toxicity associated with aggregates formed in the absence and in the presence of heme at the beginning of the aggregation process and after 15 d. The results are shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When doxycycline was added to the ␤2-m solution in the absence of the organic co-solvent but in the presence of phosphate buffer and NaCl, we found very minor changes in the be detected only for the 15 N-1 H correlation of the Phe-22 residue, whereas a number of other backbone amide crosspeaks exhibited distinct and progressive amplitude changes (supplemental Fig. 2).…”
Section: Titration Of the Inhibition Of ␤2-m Fibrillogenesis By Differ-mentioning
confidence: 88%
“…So far it has been shown that tetracyclines are able to antagonize the infectivity of the PrP sc aggregates (9), to inhibit in vitro the aggregation of amyloidogenic variants of transthyretin (10), the amyloid-␤ peptide fibrillogenesis (11,12), and amylin fibrillogenesis both in vitro (13) and in vivo (14). The generic anti-aggregation property of tetracyclines has been confirmed in the fibrillogenesis of myoglobin (15), a protein that, although not amyloidogenic in humans, represents a very informative model of the mechanism of conversion of globular proteins into fibrillar assemblies.…”
mentioning
confidence: 94%